The Role of Stigma, Perceived Social Support, and Task-Oriented Coping Style in Relation with Life Satisfaction in Primary Caregivers of Children with Epilepsy: A Multiple Mediation Analysis - Ali Mohammad Parviniannasab; Fateme Dehghani; Ahmadreza Bazyari; Mohammad-Rafi Bazrafshan (Iranian Journal of Psychiatry)
Objective: Stigma exacerbates poorer life satisfaction among caregivers of children with epilepsy (CWE); however, the underlying reasons for this connection are still not fully understood. This research aimed to investigate how coping strategies and social support can impact the connection between stigma and life satisfaction. Method: A cross-sectional descriptive study was conducted on 210 primary caregivers of CWE from August to November 2023. The participants were selected through convenience sampling. The study included information on participants' demographics (such as gender, age, education level, duration of epilepsy, age of onset, seizure frequency) and four established self-report questionnaires. Caregivers completed self-report scales of perceived social support, stigma, life satisfaction, and coping style. We used the PROCESS 4.1 macro proposed by Hayes to analyze the direct and indirect associations between variables. In addition, SPSS-27 software was used to conduct Pearson correlation. Results: The research findings confirmed that both perceived social support and task-oriented coping mechanisms played a mediating role in the connection between stigma and life satisfaction (β perceived social support = -0.11; 95% bootstrap CI: -0.12 to -0.02; β task-oriented coping = -0.14; 95% bootstrap CI: -0.26 to -0.05), respectively. Furthermore, the results of serial mediation analyses revealed that the link between stigma and life satisfaction is influenced by perceived social support and task-oriented coping in a sequential process (B = -0.029, 95% bootstrapped CI: -0.060 to -0.006). Conclusion: These findings shed light on the role of perceived social support and task-oriented coping as serial mediators of the relationship between stigma and life satisfaction. Thus, identifying and correctly understanding the sources of support, as well as teaching effective task-oriented coping through mental health professionals, is necessary to reduce the stigma experienced by these caregivers and improve life satisfaction.